Effect of High-Pressure Processing on Proteolysis, Texture and Sensorial Attributes of Raw Ewe’s Cheeses Throughout Storage - Rita S. Inácio; Maria J. P. Monteiro; José A. Lopes-da-Silva; Jorge A. Saraiva; Ana M. P. Gomes (Applied Sciences)
Serra da Estrela cheese, with a Protected Denomination of Origin (PDO), is one of the most appreciated traditional raw milk Portuguese cheeses, and it is well known for its unique flavor and texture, which are derived from the use of raw ewe’s milk and its production process. In this work, 45-day-old ripened Serra da Estrela cheeses were processed by high-pressure processing (HPP) at 600 MPa/6 min (P1), 450 MPa/6 min (P2) and 450 MPa/9 min (P3) to study the effect of HPP initially and during 15 months of storage at 4 °C. The proteolysis indexes were, in general, lower in the HPP-treated cheeses than in the control cheeses. The P1 cheeses kept their ripening extension index throughout the 15 months of storage close to that of non-processed cheese at month 0. Progression of the ripening depth and free amino acids indexes was also slowed down by HPP. HPP had no immediate effect on the cheese texture parameters, and minor changes were found up to 3 months of storage; moreover, the P2 cheeses maintained their hardness and consistency levels during the 15-month storage period at values close to those of the control cheeses at month 0. Sensory evaluation by trained panelists showed that the P2 cheeses were softer than the control cheeses; furthermore, for the P3 cheeses, there were no observed treatment effects on the sensory attributes evaluated at the end of storage. Overall, the results uphold the potential of HPP in rendering Serra da Estrela cheese proteolysis levels similar to those of control cheese at 45 days of ripening with minor effects on texture.